2015
DOI: 10.18865/ed.25.3.245
|View full text |Cite
|
Sign up to set email alerts
|

The National Institute on Aging Health Disparities Research Framework

Abstract: <p><strong>Objective</strong>: Development of a new framework for the National Institute on Aging (NIA) to assess progress and opportunities toward stimulating and supporting rigorous research to address health disparities.</p><p><strong>Design:</strong> Portfolio review of NIA’s health disparities research portfolio to evaluate NIA’s progress in addressing priority health<br />disparities areas.<br /><strong></strong></p><p><stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
206
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 273 publications
(229 citation statements)
references
References 49 publications
1
206
0
2
Order By: Relevance
“…We defined health disparities within the National Institute on Aging health disparities research framework to include health and health system quality disparities related to race, ethnicity, culture, socioeconomic status, environment, geography, sex, or gender identity (Hill et al 2015). Because other reviews have identified health and health system quality disparities related to disability (i.e., between individuals with ASD and controls; Tregnago and Cheak-Zamora 2012; Cashin et al in press), we excluded studies which exclusively focused on disability-related health disparities from our review.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We defined health disparities within the National Institute on Aging health disparities research framework to include health and health system quality disparities related to race, ethnicity, culture, socioeconomic status, environment, geography, sex, or gender identity (Hill et al 2015). Because other reviews have identified health and health system quality disparities related to disability (i.e., between individuals with ASD and controls; Tregnago and Cheak-Zamora 2012; Cashin et al in press), we excluded studies which exclusively focused on disability-related health disparities from our review.…”
Section: Methodsmentioning
confidence: 99%
“…Health status and life expectancy vary across the population (Hill et al 2015), and emerging evidence suggests that people with autism spectrum disorder (ASD) experience heightened morbidity and early mortality compared to those without ASD (Croen et al 2015; Hirvikoski et al 2016; Cashin et al in press). Well-documented disparities in access to diagnostic and early intervention services for ASD (Ennis-Cole et al 2013; Magaña et al 2013; Mandell et al 2007) suggest that individuals with ASD who are otherwise disadvantaged by society—including those who experience disadvantage related to their race, ethnicity, culture, socioeconomic status, environment, geography, sex, or gender identity—may experience even greater disparities in health status and life expectancy.…”
mentioning
confidence: 99%
See 3 more Smart Citations